the MIND diet handout - Smith, Brittany; Craven, Kay; Kolasa, Kathryn M. (My University, 2020)
The 2 page handout was designed to help patients/clients visualize an eating approach emphasizing food found in reducing dementia risk and slowing cognitive decline. It is based on the book, "Diet for the Mind" by Martha Clare Morris. The front side is a plate divided into protein, starches, and no starchy vegetables with a side of berries, nuts and wine. It also lists foods to limit. The back side is a tool to assess an individual's diet for its adherence to the MIND food categories and servings. It has a place for the user to write a SMART Goal.
Keywords: MIND diet; diet assessment